Stunting di Indonesia: Tantangan dan Solusi di Era Modern - Oslida Martony (Journal of Telenursing (JOTING), 2023)
This research aims to investigate the problem of stunting in Indonesia and analyze the relevant challenges and solutions in dealing with this problem in the new era. Stunting, which is defined as stunted growth in children under the age of five, has become a serious problem in Indonesia with long-term adverse effects on children's health and development. The method used is a qualitative method with descriptive analysis. The results of the study show that the stunting rate in Indonesia is still high, even though there has been a decline in recent years. The challenges faced in efforts to reduce stunting include long-term malnutrition, ineffective parenting styles, inadequate knowledge about balanced nutritional diets, lack of postpartum care, persistent infectious diseases in children, and poor sanitation. In facing this challenge, comprehensive and integrated solutions are needed, including specific and sensitive interventions, cross-sectoral approaches, empowering women, and making policies and programs that support stunting prevention. In conclusion, stunting in Indonesia remains a complex problem that requires coordinated cross-sector collaboration. In addressing this challenge in the modern era, a holistic and sustainable intervention strategy is needed to reduce the prevalence of stunting and ensure optimal growth and development of children in Indonesia. Keywords: Toddlers, Nutrition, Prevalence, Solutions, Stunting, Challenges